Effect of microwave-assisted ionic liquid/acidic ionic liquid pretreatment on the morphology, structure, and enhanced delignification of rice straw. (December 2019) - Sorn, Virak; Chang, Ken-Lin; Phitsuwan, Paripok; Ratanakhanokchai, Khanok; Dong, Cheng-Di
Graphical abstract: Highlights: Microwave-[Bmim]Cl pretreatment shows the most promising result for sugar release. The lignin removal was achieved 57.02% by microwave-[Bmim]Cl pretreatment. Microwave-[Bmim]Cl pretreatment increased glucan conversion to 61.14%. The reduced CrI and LOI revealed the positive effects of pretreatment. [Bmim]Cl can be recycled and reused without using any antisolvent. Abstract: In the present study, was investigated an environmentally friendly method for pretreating lignocellulosic rice straw (RS) by using 1-butyl-3-methylimidazolium chloride ([Bmim]Cl) as an ionic liquid (IL) and 1-butyl-3-methylimidazolium hydrogen sulfate ([Bmim]HSO4 ) as an acidic-IL (Acidic-IL) under microwave irradiation (microwave-[Bmim]Cl and microwave-[Bmim]HSO4 ). The conversion of lignocellulosic biomass into simple sugars requires both efficient pretreatment and hydrolysis enzymes to produce biofuels and specialty chemicals. Therefore, the applied [Bmim]Cl, [Bmim]HSO4, microwave-[Bmim]Cl, and microwave-[Bmim]HSO4 to improve hydrolysis yields. Structural analyses of the pretreated solids were performed to understand the synergistic effects of [Bmim]Cl, and [Bmim]HSO4 pretreatment under microwave irradiation (microwave-[Bmim]Cl and microwave-[Bmim]HSO4 ) on the efficiencies of enzymatic hydrolyses. The results of a chemical composition analysis of untreated and all pretreated RS samples by using the difference pretreatment methods showed that significant lignin removal was achieved using microwave-[Bmim]Cl (57.02 ± 1.24%), followed by [Bmim]Cl only (41.01 ± 2.67%), microwave-[Bmim]HSO4 (20.77 ± 1.79%), and [Bmim]HSO4 -only (16.88 ± 1.14%). The highest glucan yield and xylan conversion achieved through the enzymatic saccharification of microwave-[Bmim]Cl-regenerated cellulose was consistent with the observations obtained from a structural analysis, which indicated a more disrupted, amorphous structure, with lowered crystallinity index (CrI) and lateral order index (LOI) of cellulose polymers. Thus results demonstrated that the pretreatment of lignocellulosic biomass with [Bmim]Cl under microwave irradiation has potential as an alternative method for pretreating lignocellulosic materials.